GEODYNAMIC CONDITIONS OF FORMATION OF SARMATIAN DEPOSITS OF THE GERAKLEYSKY PLATEAU (THE SOUTHWEST CRIMEA) - IVANOV, V.Yе.; LOMAKIN, I.E.; TOPOLYUK, A.S.; KOCHELAB, V.V.; BOLDYREV, S.N. (Institute of Geological Sciences, NAS of Ukraine, 2013)
Sometimes the dislocation of middle sarmatian deposits of Geraclean plateau are very intensive. The long-wave folds and uplifts are discovered. The Litological structure of Sarmatian thicknesses is extremely various, especially in zones of influence of regional deep faults. Heavy hydrocarbons are found in east part of the Gerakleysky plateau in bentonite-montmorilonitic clays and limestone. The given materials indicate a good oil and gas potential of the territory and allow to consider this area as perspective in aspect of detection of new fields of hydrocarbons – the most important raw resource of development of economy ofUkraine.